ANALYSIS OF THE TECHNICAL-TATICS ACTIONS OF THE GOALKEEPER-LINE IN FUTSAL GAMES (Fiep Bulletin - online, 2015)
There is an agreement that every team starts with a great goalkeeper. This position is very important in Futsal since it requires an expert. When the rule made it possible to the goalkeepers perform out of the area using their feet, many alternative tatics were adapted by the trainers and the goalkeeper became more active in the team. During the trainings there was the possibility of the participation of the goalkeeper in ending a goal or articulating the moves. Considering that one of the alternatives for the improvement of the players performance is the increase of their technical-tatic behavior during the game, an analysis was done based on technical-tatic actions of Futsal line-goalkeepers who participated of the Brazilian Junior Teams Championship. The data from the observation spreadsheet were analyzed from the 7 videos of games. This work had as purpose to analyze the line-goalkeeper technical-tatic behavior and check the frequency of his own participation. It can be seen from the study a frequent line-goalkeeper set in motion in Futsal games in each 1'36”. In these games they reached 69% of right technical hits during their performance. It was also verified in the study that 82% of the line-goalkeepers actions were achieved in the central court corridor making it possible to them the favorable conditions of endings and passes changes. Finally, it was confirmed the hypothesis that goalkeepers are mostly set in motion when the scoreboard is unfavorable to the respective teams.
Keywords: futsal; goalkeepers; scout.